Relationship between root system-soil C:N:P and soil microbial diversity at different evolutionary stages of Caragana tibetica scrub in arid desert grassland, Northern China - Han, Min; Liang, Yumei; Gao, Yong; Yang, Wenyuan; Guo, Yuefeng (Frontiers in Plant Science, 2024)
Scrub root systems play a crucial role in preventing soil erosion and nutrient loss.However, the effects of the root system configuration on soil nutrient dynamics and microbial changes at various evolutionary stages remain poorly understood. In this study, we investigated the relationship between soil physical and chemical properties and the diversity of bacteria and fungi throughout the evolutionary stages of the scrub root systems.This was achieved through a combination of whole-root excavation and root tracing techniques. The results indicated that root diameter was the main factor contributing to the continuous increase in carbon (C) : phosphorus (P) and nitrogen (N) : P ratios as the scrub sand pile developed. The soil organic carbon (SOC), total soil nitrogen (TN), and total soil phosphorus (TP) contents in the soil in the four evolutionary stages were the highest during the developmental stage, but the change in TP content was not statistically significant (P > 0.05). Partial least squares path modeling and redundancy analysis (RDA) analyses indicated that root system stoichiometric C and N contents were positively correlated with microbial diversity (R 2 = 0.85). There was no correlation between the evolutionary stage and soil nutrient TN, whereas soil nutrient TN was negatively correlated with microbial diversity (R 2 = -0.92). These findings elucidate the relationship between the evolutionary stage of root chemical measurement characteristics, soil elements and microorganisms as well as their subsequent effects on root elemental composition and microbial diversity. This study enhances the current understanding of plant-soil interactions in desert steppe ecosystems.